THE EFFECT OF TWO STAY TWO STRAY (TSTS) COOPERATIVE LEARNING ON STUDENTS’ VOCABULARY MASTERY IN ENGLISH - Tri Rositasari; Dwi Rara Saraswaty; Rona Monica (English Review: Journal of English Education, 2025)
The acquisition of vocabulary is critical for mastering English as a foreign language, particularly among young learners. This study investigates the impact of the Two Stay Two Stray (TSTS) cooperative learning technique on vocabulary mastery among fourth-grade students at SDN 34 Palembang. Employing a quasi-experimental design, the research involved 48 students selected through purposive sampling, divided into experimental and control groups. Data were collected with vocabulary tests and student questionnaires, with statistical analysis performed using t-test. The findings revealed a significant improvement in vocabulary mastery among students taught using the TSTS technique, evidenced by a post-test mean score of 72.71 for the experimental group, compared to 62.13 for the control group. The t-test significance value of 0.008 (<0.05) led to rejection of the null hypothesis. Consequently, the study concluded that the TSTS technique positively influences vocabulary achievement in fourth-grade students, fostering an engaging and interactive learning environment that enhances vocabulary mastery and student motivation.